The impact of agriculture on tropical mountain soils in the western Peruvian Andes: a pedo-geoarchaeological study of terrace agricultural systems in the Laramate region (14.5° S) - Leceta, Fernando; Binder, Christoph; Mader, Christian; Mächtle, Bertil; Marsh, Erik; Dietrich, Laura; Reindel, Markus; Eitel, Bernhard; Meister, Julia (Soil, 2024)
This integrated pedo-geoarchaeological study focuses on three abandoned pre-Hispanic terrace agricultural systems near Laramate in the southern Andes of Peru (14.5° S), aiming to unravel the pedological and land-use history of the region, which served as a significant agricultural hub during pre-Hispanic times. The key objectives of the investigation involved contextualizing the former agricultural management system within its geomorphological and palaeoecological framework and assessing the impact of agricultural practices on soil development and quality by comparing non-irrigated agricultural terrace soils with their undisturbed palaeo-pedological counterparts. The Laramate terrace complex, with its diverse terrace systems and varied geomorphological and geological settings, provided an ideal setting for the investigation. This comprehensive examination integrated a range of methodologies, including field surveys, digital mapping, and geomorphological analysis based on GIS and remote sensing applications, soil analysis (e.g. grain size, bulk chemistry, nutrient budget), plant microfossils (phytoliths and starch), and radiocarbon dating. - - In the Laramate region, the geomorphological setting of terrace agricultural systems promotes their optimal functioning. The terraces are often located in sun-sheltered areas with western exposure on middle and lower slopes or valley bottoms, which mitigate intense solar radiation, reduce evapotranspiration, increase soil moisture, and minimize erosion. The study identifies three soil groups in the Laramate region: Phaeozems, Andosols, and Anthrosols. Unique characteristics of Phaeozems challenge typical descriptions, influenced by factors such as climatic seasonality, vegetation, fauna, lithology, and aeolian inputs. The terrace soils in the Laramate region are classified as Terric Anthrosols, showing no significant degradation even after long-term use. Their balanced acidity and nutrient levels support Andean crop cultivation. Traditional non-mechanized tools, such as the chaquitaclla and rucana, likely minimized soil disruption. The terrace tillage horizons have high organic matter, indicating intentional organic manuring. Phytolith concentrations suggest intensive agricultural activity, particularly maize cultivation, with varying patterns suggesting changes in cultivation, fertilization, or mulching practices over time. Starch grain identification aligns with phytolith analyses, reinforcing maize's significance in the region. Although the use of animal-origin fertilizers requires further investigation, there is no evidence of nutrient maintenance through seasonal burning. Irrigation was minimal, and the abandonment of the pre-Hispanic cultivation system was unlikely due to soil exhaustion or terrace instability. - - Overall, the pre-Hispanic history of terrace agriculture in the Laramate region extends over four development phases, reflecting dynamic interactions between environmental, cultural, and agricultural factors. The initial phase, from the Formative Paracas period to the Early Nasca period (800 BCE-200 CE), witnessed the establishment of agricultural terraces with simple terrace architecture, while the Middle Horizon (600-1000 CE) saw systematic areal expansion influenced by the Wari culture. Adaptations to drier conditions included terrace agriculture on volcanic soils. The Late Intermediate period (1000-1450 CE) witnessed hydrological variability and further terrace expansion to lower altitudes and less agriculturally suitable locations. The final phase, marked by the onset of the Hispanic colonial period in 1535 CE, saw the gradual abandonment of terrace agricultural systems due to demographic shifts and reorganization of production systems. Despite this, the historical trajectory underscores the adaptability and resilience of pre-Hispanic communities in the Laramate region, showcasing innovative terrace agriculture as a means of coping with changing environmental conditions across diverse landscape units.
Gesehen am 10.04.2025